Organizing Possible Futures: A Systematic Review on Dis/ability Justice Frameworks to Design Equity-Oriented Inclusive Teacher Education Programs - Ko, Dosun; Krichevsky, Boris; Lim, Sumin; Mawene, Dian (Review of Educational Research, 2024)
In the U.S. school system, Black, Indigenous, and People of Color (BIPOC) students often experience multiple forms of marginalization at the intersection of racism, ableism, and other forms of subjugation. To reform dysfunctional school systems, teacher education programs must create transformative spaces to nurture future educators committed to equity. These educators then will be equipped to dismantle the (in)visible racist and ableist structures within education systems and envision new alternative futures. Drawing on critical learning sciences and dis/ability justice-oriented theoretical approaches, we conducted a systematic literature review of 11 empirical studies to examine how teacher preparation programs are informed by dis/ability justice theoretical lenses. We synthesized how dis/ability justice-oriented teacher preparation programs organized transformative learning environments aimed at disrupting color-evasive and pathologizing discourses. We discussed the findings on how these programs conceptualized dis/ability, their applications of these conceptualizations in practice, and the transformative learning outcomes for preservice teachers.
Keywords: Black, Indigenous, and People of Color (BIPOC); Education Systems; School System; Teacher Education Programs; Equity-Oriented Inclusive